Exposure to the genocide news, boycott campaigns on social media, and their consequences on social attitudes - Suryaning Hayati; Nurul Aidin; Ryan Ardhito Hadyan (Master of Communication Science Program, Universitas Diponegoro, 2025)
The Israeli Genocide against Palestine was widely reported in online mass media. The media's construction of this event reveals violations of international humanitarian law. The audience's rage is conveyed through social media, funding campaigns, and exclamation to influence UN decisions. Continuous exposure to news and social media campaigns eventually leads the public to boycott products that are confirmed to support Israel. Based on this fact, this study intends to investigate the impact of online news exposure and social media campaigns on social attitudes. Through a survey of 400 respondents, data were analyzed using multiple linear regression. The partial test results obtained: 1) online news exposure influences social attitudes with an estimated value of 0.137; 2) Social media campaigns also influence social attitudes with an estimated value of 0.801. Both results can be interpreted as having a positive influence on variables. The results of the F test show that online news exposure and social media campaigns are considered to have a simultaneous influence on social attitudes. This study offers implications for theoretical advancement in digital activism and practical recommendations for strengthening public communication strategies in humanitarian issues.